Poorer health - shorter hours? Health and flexibility of hours of work - Johannes Geyer; Michał Myck (Institute for the Study of Labor (IZA), 2010)
We analyse the role of health in determining the difference between desired and actual hours of work in a sample of German men using the Socio-Economic Panel Data for years 1996-2007. The effects of both self-assessed health and legal disability status are examined. About 60% of employees report working more than they would wish with the mean difference of -3.9 hours/week. We estimate static and dynamic model specifications allowing for autoregressive nature of the dependent variable and testing for the role of lagged health status. Important differences are found between east and west German Länder. In the west we find statistically significant role of general health measures in determining the disequilibrium. Employees in bad health want to work on average by about 0.4 hour/week less according to the static specification, and by about 1 hour/week less if dynamics of health and of the disequilibrium are taken into account. This is respectively 10% and 25% of the mean difference. We find no effects of legal disability status on the disequilibrium which we interpret as a reflection of stronger legal position of disabled employees. In both east and west we find significant state dependence in the hours disequilibrium.
Keywords: J21; J14; 330; hours worked; health; disability; labour market flexibility; Arbeitszeitflexibilisierung; Gesundheit; Meinung; Erwerbsunfähigkeit; Schätzung; Deutschland